Waste electrical and electronic equipment (WEEE) management: An analysis on the australian e-waste recycling scheme. (1st October 2018) - Dias, Pablo; Bernardes, Andréa Moura; Huda, Nazmul
Abstract: Solutions for the global arising waste electrical and electronic equipment (WEEE) challenge are constantly being proposed and implemented worldwide. To be in pace with the world, Australia debuted the national computer and television recycling scheme (NTCRS) in 2012 and has already diverted thousands of tons of WEEE away from landfill. In this study, the structure, collection methods and recycling processes of the scheme are analyzed considering the perspective of different agents involved in the scheme. The recycling facilities working directly under the scheme as first stage recyclers are identified and their operational procedures are investigated. The results show that there are currently 31 facilities, that they mainly process waste using manual sorting and manual dismantling; and that material recovery requires further downstream processing, which is undertaken domestically and internationally. The exports have been growing since the commencement of the scheme and should continue to grow unless incentives for domestic downstream processing are implemented. Moreover, this study analyzes the roles and responsibilities of the different agents working under the NTCRS. It is shown that local councils are important e-waste collection channels, but they hold little responsibility within the legal framework of the scheme. Furthermore, co-regulatory arrangements are responsible for assuring that the outcomes of the scheme are achieved, yet their responsibility of auditing the recycling and recovering processes stops at first stage recycling. Finally, this study reveals challenges and proposes solutions for the scheme, which, when perfected, can be replicated as a WEEE management model for the world. Highlights: The scheme has successfully developed a collection system for continental countries. The number of NTCRS first stage recyclers was determined and they were mapped. Australia acts as a concentrator of valuable e-waste, which is then exported. Australian e-waste recyclers only undertake initial recycling processes. The current system favors international (export of waste) over domestic recycling.